2018
DOI: 10.1108/ilt-12-2016-0306
|View full text |Cite
|
Sign up to set email alerts
|

Effect of wear parameters on dry abrasive wear of RZ5-TiC in situ composite

Abstract: Purpose The purpose of this study is to increase the wear resistance of Mg alloy by adding hard ceramic particles to it. The inclusion of hard ceramic particles further strengthen the Mg alloy, resulting in higher wear resistance. Mg alloys containing Zn, rare earth and Zr exhibit high specific strength and excellent creep resistance, making them suitable for aerospace components such as aircraft gearboxes and generator housings. Design/methodology/approach In the present study, composites have been produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…They used dry sand rubber wheel abrasion wear test to compare the three-body abrasive wear resistance between NM500 steel and (Ti, Mo)Creinforced steel under applied loads of 45 and 130 N. They reported that the wear resistance of the particlereinforced steel is 1.6 times that of NM500 at the heavy load of 130 N and 1.8 times at the light load of 45 N. In Ref. [195], TiC particles were also added into RZ5 Mg alloy to improve its mechanical strength and wear resistance. They used a self-propagating high temperature synthesis technique to make the composite and tested the reinforced Mg alloy by using a pin-on-disk tribometer under dry abrasive wear conditions.…”
Section: Wear Behavior and Mechanismsmentioning
confidence: 99%
“…They used dry sand rubber wheel abrasion wear test to compare the three-body abrasive wear resistance between NM500 steel and (Ti, Mo)Creinforced steel under applied loads of 45 and 130 N. They reported that the wear resistance of the particlereinforced steel is 1.6 times that of NM500 at the heavy load of 130 N and 1.8 times at the light load of 45 N. In Ref. [195], TiC particles were also added into RZ5 Mg alloy to improve its mechanical strength and wear resistance. They used a self-propagating high temperature synthesis technique to make the composite and tested the reinforced Mg alloy by using a pin-on-disk tribometer under dry abrasive wear conditions.…”
Section: Wear Behavior and Mechanismsmentioning
confidence: 99%
“…Thus, result in improvement of wear resistance because of the improvement of the hardness. The hardness of the composite is improved from 75 to 105 VHN (Mehra et al , 2018a, 2018b, 2018c, 2018d, 2018e). The influence of the Wt.% of TiC and sliding distance for weight loss are relatively high as compared to applied load as shown in Table II.…”
Section: Resultsmentioning
confidence: 99%
“…This mechanism is similar to the general machining. As the material is separated from the RZ5-TiC composite by cutting force may weaken the grain boundaries and result in fracture of the particles that is pull out of the grains (Mehra et al , 2018a, 2018b, 2018c, 2018d, 2018e).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tribology of magnesium composite with variation in SiC particle size was investigated, and a reduction in specific wear rate at moderate conditions was observed (Huang et al , 2011). The wear analysis on TiC reinforced magnesium composite was investigated, and an improvement in wear resistance was observed (Mehra et al , 2016). The wear rate and mechanisms rely on applied parameter, and hence the identification of optimum and significant parameter influencing the same is need to be known.…”
Section: Introductionmentioning
confidence: 99%